Transmission patterns of Leishmania tropica around the Mediterranean basin: Could Morocco be impacted by a zoonotic spillover? - El Idrissi Saik, Imane; Benlabsir, Chaimaa; Fellah, Hassan; Lemrani, Meryem; Riyad, Myriam (PLoS neglected tropical diseases, 2022)
Cutaneous leishmaniasis (CL) due to Leishmania tropica is a neglected tropical disease characterized by a wide geographical distribution in the Mediterranean basin and is endemic in several of its countries. In addition, the vector Phlebotomus sergenti is abundantly present all around the basin. Its transmission cycle is still subject to debate. In some countries, the presence of an animal reservoir has been confirmed. In Morocco, CL due to L . tropica has risen since the 1980s and has spread widely to become the most abundant form of leishmaniasis in the territory. However, the anthroponotic transmission is so far the only recognized mode, despite recordings of L . tropica infection in animal hosts. In this review article, we assess the situation of CL due to L . tropica in the Mediterranean basin with a focus on Morocco and gather knowledge about any potential zoonotic transmission in the country. A concomitant zoonotic transmission could explain the persistence of the disease in areas where human protective measures combined with vector management did not help reduce the disease burden.